RADIOLOGICAL ASSESSMENT OF BONE REGENERATION DYNAMICS FOLLOWING ONE-STAGE DENTAL IMPLANTATION USING A‑PRF TECHNOLOGY - Nigora Pardaevna Mardonova, Jaloliddin Fazliddin o‘g‘li Nurmurodov; Navruz Khabibullaevich Bobonazarov (Research Focus International Scientific Journal, 2026)
Background: Immediate (one-stage) implant placement reduces total rehabilitation time but occurs during early post-extraction remodeling and may be associated with delayed healing. Advanced Platelet‑Rich Fibrin (A‑PRF) is an autologous fibrin matrix enriched with platelets and leukocytes and is used as a regenerative adjunct to stabilize the wound and deliver growth factors. Objective. To describe radiological healing dynamics 4 months after one-stage dental implantation performed with adjunctive A‑PRF. Methods. A pilot case series included 9 patients treated with immediate implant placement. Periapical radiographs were obtained at baseline and at 4 months and assessed for peri‑implant radiolucency, qualitative trabecular maturation, and signs of bone fill within the implant-socket gap. Early clinical follow-up documented soft‑tissue response and pain. Results. Follow-up radiographs demonstrated the absence of peri‑implant radiolucent zones and no radiographic signs of destructive bone resorption. Progressive trabecular consolidation and increased mineralization were observed in the surgical area. Postoperative edema and hyperemia were mild and pain complaints were limited. Conclusion. In this small pilot series, A‑PRF use during one-stage implantation was associated with favorable radiographic healing at 4 months. Controlled studies with standardized measurements (marginal bone levels, CBCT densitometry, ISQ) are recommended.